2019
DOI: 10.1021/acsbiomaterials.9b00956
|View full text |Cite
|
Sign up to set email alerts
|

Can Dental Cement Composition Affect Dental Implant Success?

Abstract: Cement-retained restorations on dental implants are a well-established method to replace missing teeth. However, undetected residual cement left during crown cementation procedures encourages microorganism growth, and it has been identified as a risk factor for peri-implant disease. Currently, there is no official guidance for dental cement selection, and the increasing variety of available compositions intensifies the complexity of the clinicians’ decision process. The present study aimed to evaluate the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…Both cements were cytotoxic to the HGF cell line (cell viability <70%) after half an hour; however, the cell viability was >70% after 24 hours in contrast to the present study. In a study by Gallegos et al, 40 similar to the present study, R (RelyX Unicem 2 Clicker) cement was highly toxic to the MC3T3E1 and HGF cell lines after 3 and 7 days.…”
Section: Discussionsupporting
confidence: 86%
“…Both cements were cytotoxic to the HGF cell line (cell viability <70%) after half an hour; however, the cell viability was >70% after 24 hours in contrast to the present study. In a study by Gallegos et al, 40 similar to the present study, R (RelyX Unicem 2 Clicker) cement was highly toxic to the MC3T3E1 and HGF cell lines after 3 and 7 days.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it is also important to highlight that cement properties can be affected by the host and conditions of the root canal microenvironment. For instance, oral bacteria can degrade the cement surface (Gallegos et al 2019), while low dentine moisture can decrease cement adhesion (Ozlek et al 2020). Hence, future studies are needed to characterize the effects of host/material interactions and cement components on properties and demonstrate that GAs' cements can induce differentiation and mineralization in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that excess cement in the periimplant tissues can be a cause of the development of periimplantitis, which is why it is recommended that the margin of the restoration be at a gingival level, to facilitate hygiene in the area, as well as perform control appointments after the restoration is placed to observe that the tissues are healthy [33] . It has also been found that the composition of the dental cement can affect the success of the implant since they can affect some cell lines that act in osseointegration, finding that only bioceramic cements achieved a viability greater than 70% for all the cell lines studied [34] , as well as another study found that resin cements, resin-modified glass ionomer cements and zinc oxide-eugenol cements show moderate to severe toxicity against gingival fibroblasts and preosteoblasts, which shows the importance of the choice of cementing material for implant survival [35] . Post-cementation residues are related to biological pathologies related to the implant.…”
Section: Cementation In Implantologymentioning
confidence: 99%